An efficient computational approach for numerical solution of non-smooth dynamical systems - Mohammad Ali Mehrpouya; Hossein Heidary (AUT Journal of Mathematics and Computing)
In this paper, an efficient computational approach based on the fantastic Simpson integral formula is developed for the numerical solution of nonsmooth dynamical equations. In the proposed approach, at first, the integral reformulation of the target problem is intended. Then, the Simpson formula is employed to discretize the obtained integral equation. It is mentioned that, the implementation of the method is simple, so, the method can be simply and quickly used to solvea wide variety of non-smooth dynamical systems arising in the various engineering models. Numerical experiments of two benchmark examples are presented at the end and the efficiency of the method is reported.